CLA Maturity Tool - Card Deck (Implementing Partners version 1) - LEARN, USAID (USAID, 2022)
USAID’s Bureau for Policy, Planning and Learning (PPL) and its support mechanism, LEARN, have developed a Collaborating, Learning, and Adapt ing (CLA) Framework and Maturity tool to help USAID missions think mor e deliberately about how to plan for and implement CLA approaches that fit the mission’s context and assist them in achieving their developm ent objectives. While the tool is intended primarily for USAID audienc es to be used in participatory self-assessment workshops, the CLA Fram ework and maturity spectrum are relevant to a wider audience. USAID’s CLA Framework identifies key components and subcomponents of daily wor k that may be opportunities for intentional, systematic, and resourced CLA. The framework recognizes the diversity of what CLA can look like in various organizations and programs while also giving CLA structure , clarity, and coherence across two key dimensions: • CLA in the Progr am Cycle: how CLA is incorporated throughout Program Cycle processes, including strategy, project, and activity design and implementation; a nd • Enabling Conditions: how an organization’s culture, business proc esses, and resource allocation support CLA integration. Recognizing th at CLA is not binary—it’s not an issue of “doing it or not doing it”—P PL and LEARN have developed a spectrum of practice for each of the 16 subcomponents in the framework. The spectrum offers examples of what i ntegration might look like at different stages: Not Yet Present, Emerg ent, Expanding, Advanced and Institutionalized. The maturity stage des criptions are only illustrative and are intended to spark reflection o n current practice and opportunities for improvements. In this resourc e, each CLA subcomponent page describes the key concepts for that topi c and includes a description of the maturity stages. Although the desc riptions were originally developed for USAID, the majority of the conc epts easily transfer or have equivalents in the partner community. For example, although organizations outside of USAID may not hold “Portfo lio Reviews” (part of the Pause & Reflect subcomponent), the majority hold some type of meeting to review programmatic progress. This is the seventh version of the CLA Framework and maturity spectrum. PPL and L EARN will continue reviewed and periodically update them based on user feedback, so if you have comments about the content, please email lea rning@usaid.gov. We would also love to hear how you’ve used this conte nt with your team or organization.